(α,ψ)-Meir-Keeler Contraction Mappings in Generalized b-Metric Spaces - Erdal Karapinar; Stefan Czerwik; Hassen Aydi (Journal of Function Spaces)
We present a fixed point theorem for generalized (α,ψ)-Meir-Keeler type contractions in the setting of generalized b-metric spaces. The presented results improve, generalize, and unify many existing famous results in the corresponding literature.